Chronic and Transient Poverty - Aubrey D. Tabuga; Christian D. Mina; Celia M. Reyes; Ronina D. Asis; Maria Blesila G. Datu (Philippine Institute for Development Studies (PIDS), 2010)
The Philippines has been posting progress in terms of poverty reduction since the early 1990s. However, reversal in the trend was observed in 2006. Further worsening of the poverty situation is expected given the various economic and natural shocks (i.e., food and fuel price hikes; global financial and economic crisis; typhoons Milenyo, Reming, Frank, Ondoy, Pepeng; and the recent El Nino) that recently hit the country. Many households, especially those that belong to the bottom 40 percent, are deemed vulnerable to these shocks. Using a panel of households from the different rounds of Family Income and Expenditure Survey (FIES) and Annual Poverty Indicators Survey (APIS) from 2003 to 2008, this paper examined the movements in and out of poverty among households. The study provided a description of the extent of chronic and transient poverty as well as the various household characteristics that discriminate among the different groups of households, including the chronic and the transient poor. A panel regression analysis was also explored to identify factors that can predict the income-based poverty status of households. Based on the descriptive and regression analyses, some insights were presented that can guide the government in the formulation of specific types of interventions to different groups of households, especially the transient poor. This is hopefully an attempt to recover the previous gains in poverty reduction and thus attain the MDG target of halving extreme poverty by 2015.
Keywords: 330; Philippines; chronic poor; transient poor; panel data; logistic panel regression; Armut; Soziale Lage; Haushaltseinkommen; Philippinen